2010
DOI: 10.1134/s106377371011006x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of circumstellar extinction in a young binary system with a low-mass companion in a noncoplanar orbit

Abstract: The cyclic activity model of a young star with the low-mass secondary component (q = M2/M1 ≤ 0.1) accreting a matter from circumbinary disk is considered. It is assumed that the orbit is circular and the disk and orbital planes are non-coplanar. Sets of hydrodynamics models of such a system have been calculated by the SPH method and then the variations of the circumstellar extinction and phase light curves were determined. The calculations showed that depending on the model parameters and orientation of the sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…The flow of matter in binary systems accreting material from protoplanetary disks has been simulated numerically in many studies [7][8][9][10][11][12][13][14][15][16][17]. The simulation results indicate the following major flow elements in these systems: circumstellar accretion disks around the system components, a rarefied area in the central parts of the protoplanetary disk adjoining the binary, and a complex system of gas-dynamical flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow of matter in binary systems accreting material from protoplanetary disks has been simulated numerically in many studies [7][8][9][10][11][12][13][14][15][16][17]. The simulation results indicate the following major flow elements in these systems: circumstellar accretion disks around the system components, a rarefied area in the central parts of the protoplanetary disk adjoining the binary, and a complex system of gas-dynamical flows.…”
Section: Introductionmentioning
confidence: 99%
“…For reverse rotation to occur, the angular momentum delivered to the disk by the falling matter must be opposite to the angular momentum of the system. Numerical simulations of these systems have been performed in various studies [7][8][9][10][11][12][13][14][15][16][17], have not indicated the appearance of reversed accretion disks in binary systems for a wide range of parameters. In addition, analysis of the flow structure that forms in the vicinity of a young binary indicates that flows directed opposite to the motion of the components can exist [15].…”
Section: A Model For the Formation Of A Reversed Accretion Diskmentioning
confidence: 99%
“…These authors showed that the column density of matter along the line of sight can be a complicated function of the phase of the orbital period. Similar calculations have been continued in our subsequent papers (Demidova et al 522 T. , Grinin et al 2010a. We considered two types of binary orbits.…”
Section: Introductionmentioning
confidence: 75%
“…Calculations using the model based on the smoothed-particle hydrodynamics method (SPH) show that the lowmass component is the main accretor in the system [8][9][10][11][12], while the model based on the total variation diminishing (TVD) scheme gives an opposite result (see Refs. [13,14]).…”
Section: Introductionmentioning
confidence: 99%